Persistence in ESG and Conventional Stock Market Indices - Guglielmo Maria Caporale; Luis A. Gil-Ala\~na; Alex Plastun; Inna Makarenko (Center for Economic Studies and Ifo Institute (CESifo), 2021)
This paper uses R/S analysis and fractional integration techniques to examine the persistence of two sets of 12 ESG and conventional stock price indices from the MSCI database over the period 2007-2020 for a large number of both developed and emerging markets. Both sets of results imply that there are no significant differences between the two types of indices in terms of the degree of persistence and its dynamic behaviour. However, higher persistence is found for the emerging markets examined (especially the BRICS), which suggests that they are less efficient and thus offer more opportunities for profitable trading strategies. Possible explanations for these findings include different type of companies' `camouflage' and `washing' (green, blue, pink, social, and SDG) in the presence of rather lax regulations for ESG reporting.
Keywords: C22; G12; 330; stock market; ESG; persistence; long memory; R/S analysis; fractional integration